ROLE OF MEDIA IN PROTECTING JUSTICE - Balakrishna, T. (International Journal of Psychosocial Rehabilitation, 2019)
The research paper aims to understand the effects and impact of media in the process of securing justice. The author aims to analyze the present scenario with respect to use of media in various manners though various mediums to and how it can be used to the benefit of the people in the process of administration of justice. Media is said to be the fourth pillar of democracy. It has great influence on the opinions formulated by people regarding various issues in the country and around the world. Media, in its various forms, portrays these issues which affect the perception of the events. Such powerful influence must be used for the betterment of the society. This can be done by using media in the administration of justice. This paper analyzes the effects of media and its intervention in the process of administration of justice. The author aims to understand this relationship with the help of various cases with inter alia respect to freedom of press as per the constitutional provisions and also throws light upon the practice of media trials and its effects on the process of administration of justice.